Designing A 360-Degree E-Panorama Virtual Tour for the Introduction of Campus Using Theasys - Sari, Indah Purnama; Sulaiman, Oris Krianto; Apdilah, Dicky (Journal of Innovation in Research, Education and Culture (JIREC), 2025)
This study aims to design a 360-degree e-panorama virtual tour for campus introduction using Theasys. The virtual tour serves as an interactive platform to provide prospective students, visitors, and stakeholders with an immersive campus experience. The development process includes capturing high-quality 360-degree images, integrating them into Theasys, and enhancing user interaction through hotspots, navigation elements, and multimedia integration. The research evaluates the effectiveness of the virtual tour in improving users' understanding and engagement with campus facilities. The results indicate that the designed e-panorama virtual tour significantly enhances the campus introduction experience by providing an accessible and visually engaging platform.